The Influence of Academic Supervision of School Heads and Work Environment on Teacher Job Satisfaction - Winaliyah; Harapan, Edi; Kesumawati, Nila (Jurnal Pendidikan Tambusai, 2021)
This study aims to: 1. determine the effect of principal academic supervision on teacher job satisfaction; 2. knowing the work environment on teacher job satisfaction; 3. to know the effect of principal's academic supervision and work environment on teacher job satisfaction. The research method used is a quantitative method. The results of this study indicate that: 1. There is an influence between the principal's academic supervision on teacher job satisfaction; 2. There is an influence between the work environment on teacher job satisfaction; 3. There is an effect of principal academic supervision and work environment on teacher job satisfaction.